2014
DOI: 10.1016/j.neuroimage.2013.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus activity dissociates proactive and reactive inhibition in patients with Parkinson's disease

Abstract: a b s t r a c t a r t i c l e i n f oModels of action selection postulate the critical involvement of the subthalamic nucleus (STN), especially in reactive inhibition processes when inappropriate responses to a sudden stimulus must be overridden. The STN could also play a key role during proactive inhibition, when subjects prepare to potentially suppress their actions. Here, we hypothesized that STN responses to reactive and proactive inhibitory control might be driven by different underlying mechanisms with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 51 publications
5
64
1
1
Order By: Relevance
“…These decreases prematurely return to resting levels during NoGo trials that require complete response inhibition. Though it is unclear if the return to baseline observed during the NoGo trials is due to an increase in an anti-kinetic signal or an attenuation of a pro-kinetic signal, the relative power differences between movement trials and NoGo trials as well as the timing of the STN beta power changes are consistent with previous studies investigating STN beta activity when motor and non-motor actions are stopped (Kühn et al, 2004; Ray et al, 2012; Alegre et al, 2013; Bastin et al, 2014; Benis et al, 2014; Wessel et al, 2016; Zavala et al, 2017b). Of note, the reductions in STN beta band power during each movement trial were accompanied by a significant reduction in beta band spiking entrainment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These decreases prematurely return to resting levels during NoGo trials that require complete response inhibition. Though it is unclear if the return to baseline observed during the NoGo trials is due to an increase in an anti-kinetic signal or an attenuation of a pro-kinetic signal, the relative power differences between movement trials and NoGo trials as well as the timing of the STN beta power changes are consistent with previous studies investigating STN beta activity when motor and non-motor actions are stopped (Kühn et al, 2004; Ray et al, 2012; Alegre et al, 2013; Bastin et al, 2014; Benis et al, 2014; Wessel et al, 2016; Zavala et al, 2017b). Of note, the reductions in STN beta band power during each movement trial were accompanied by a significant reduction in beta band spiking entrainment.…”
Section: Discussionsupporting
confidence: 86%
“…The STN receives afferent connections from cortical regions involved in cognitive control (Alexander et al, 1986; Aron et al, 2007; Kelley et al, 2018), and projects efferent connections to other basal ganglia structures involved in movement inhibition (Albin et al, 1989; DeLong, 1990). Beta oscillations (10–30 Hz) within the STN regulate both motor and non-motor actions and increase when individuals must cancel or slow down a pre-planned action (Kühn et al, 2004; Brittain et al, 2012; Leventhal et al, 2012; Ray et al, 2012; Alegre et al, 2013; Bastin et al, 2014; Benis et al, 2014; Wessel et al, 2016; Herz et al, 2017; Zavala et al, 2017b). Theta oscillations (2–8 Hz) and spiking activity in the STN also increase when individuals are making decisions in the presence of conflict (Zaghloul et al, 2012; Zavala et al, 2013), and importantly, conflict-related increases in theta oscillations are coherent with theta activity in the mPFC (Zavala et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This points toward an increased effort to carry out successful behavioral inhibition in those individuals with increased methylation of PPM1G . The subthalamic nucleus is a basal ganglia structure whose functions include transmission of inhibitory cortical signals to basal ganglia, including the striatum (46, 50, 51). Several studies have suggested that the right subthalamic nucleus and right inferior frontal gyrus are correlated with response inhibition, suggesting that they form a frontal-subcortical pathway of control inhibition (40, 45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the right subthalamic nucleus and right inferior frontal gyrus are correlated with response inhibition, suggesting that they form a frontal-subcortical pathway of control inhibition (40, 45, 46). The right-lateralized subthalamic nucleus and inferior frontal gyrus have been used as regions of interest for response inhibition tasks (i.e., the stop signal task and go/no-go task) in studies reporting compromised impulse control in alcohol-dependent individuals (37, 38) and reduced ability to cancel prepotent responses (47), as well as in lesion studies (48), deep brain stimulation studies (49), and fMRI studies (50) of response inhibition in individuals with Parkinson's disease. Studies of in vivo deep brain stimulation of the sub-thalamic nucleus in Parkinson's patients (51) and in animal models (52) have shown a decrease in craving and regulation of substance preference, indicating the involvement of this brain region in neural processes that underlie addictive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation